Clinical Case of Mallory - Weiss Syndrome in a Child - Ye.V. Prokhorov; Ye.A. Belskaya; M.A. Matsynina; A.S. Poshekhonov (Zaslavsky O.Yu., 2013)
Clinical case of Mallory - Weiss syndrome in a 5-year-old child is described.